Založení malého podniku - Sysel, Vojtěch (Vysoké učení technické v Brně. Fakulta podnikatelská, 2018)
Diplomová práce se zabývá návrhem podnikatelského plánu na založení hotelu ve Velkém Meziříčí. Práce se skládá ze tří částí. V první části jsou uvedeny teoretické přístupy, na které je navázáno průzkumem trhu, z něhož v části poslední na základě použitých aplikací vznikl podnikatelský návrh.

The diploma thesis deals with the business plan proposal of establishing a hotel in Velké Meziříčí. The thesis consists of three parts. In the first part, there are theoretical approaches presented. These are connected with the market research. Based on the market research, the business plan is created.
Establishing of the Small Company
Keywords: Založení malého podniku; podnikatelský plán; podnikatelský model; hotel; analýza; průzkum trhu.; Creating of small business; business plan; business model; hotel; analysis; market research.